Sustaining rural livelihoods: on-farm climate-smart adaptation measures among smallholder farmers in rural Ghana (2016)
Rural livelihoods, incidence of poverty and climate change are intricately connected in the Offinso Municipality in the Ashanti region of Ghana. Conscious of the vagaries of climate change, smallholder farmers have developed adaptation measures to sustain their subsistent livelihoods. This paper examines the various on-farm adaptation measures among smallholder farmers in the Offinso municipality with the view to drawing lessons for effective policy making and implementation. A triangulation of quantitative and qualitative research design and a non-probability purposive sampling technique were used. On the basis of populations, 300 interviewer-administered questionnaires were used to collect data from smallholder farmers in 6 out of the 24 farming communities in the study area. Data generated were analyzed using thematic analyses of issues as well as through the use of cross and frequency tables, Chi-square test of association and regression at α0.05. Farmers undertook some on-farm management practices such as efficient management of irrigation system while substantially, 33.0% of the respondents did not engage in any of the soil water and moisture conservation practices. However, Pearson’s chi-square (χ2) value of 65.6 with a Cramer’s V value of 0.288 revealed a significant association between on-farm crop management activities and soil nutrients conservation. This paper recommends vigorous direction of extension work by the Department of Food and Agriculture towards harnessing the identified on-farm climate-smart adaptation measures in the study area for sustainable food production.